Case Report: A Pancreatic Ductal Adenocarcinoma Patient With Concurrent Targetable Somatic Novel KANK1-ALK, UPP2-NTRK3 Fusion, and Pathogenetic Germline BRCA Mutation - Meng, Fan; Lu, Le; Tan, Yuan; Duan, Qianqian; Lu, Hongwei (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is presently one of the cancers with the worst survival rates. The current treatment options for PDAC are relatively scarce due to insufficient understanding of molecular characteristics and subtypes of PDAC. Based on next-generation sequencing (NGS), we firstly presented a case about a KRAS wild-type pancreatic ductal adenocarcinoma patient harboring a concurrent targetable rare somatic novel KANK1-ALK, UPP2-NTRK3 Fusion, and pathogenetic Germline BRCA Mutation. These two novel fusion statuses were assayed by immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH). Our findings demonstrated that comprehensive and systematic screening of PDAC for actionable genomic alteration may substantially improve the therapeutic prospects for a sizeable fraction of patients with PDAC. To improve the management of PDAC in an era of precision medicine, it is important to identify subsets of patients who can benefit from targeted therapies.